Zdravila proti astmi - Kržan, Mojca (Medicinski razgledi, 2012)
The incidence ofbronchial asthma is very high in paediatric as well as in the adult population. Nevertheless, life style changes and adequate pharmacotherapy enables asthma patients to live normal, healthy life. rf the disease is mild the drugs are usually taken by inhalations, while for more severe form of disease systemic application of drugs either oral or by injecting is necessary. Anti-asthma drugs are divided into two groups: controllers, which prevent asthma attacks and healers that are applied when the disease deteriorates. Pharmacological classification divides anti-asthma drugs into bronchodilators (adrenergic agonists, xantines, cisteninyl-Ieukotriene antagonists, antimuscarinic drugs) , anti-inflammatory drugs (corticosteroids) and biologic drugs (omalizumab).
Keywords: asthma; Ekspektoransi; pharmacotherapy; astma; bronchodilators; therapy; zdravljenje; zdravila; antiinflammatory drugs; drug; bronhodilatatorji; protivnetna zdravila